Nutritional Value of Algerian Breed Ewe's Milk Related to its Mineral Content - Yabrir, Benalia; Hakem, Ahcene; Mostefaoui, Abdellah; Titouche, Yacine; Bouzidi, Abdelkader; Mati, Abderrahmane (Pakistan Journal of Nutrition, 2014)
The mineral content and its distribution among soluble and colloidal phases of milk from two ewe’s breed (Ouled-Djellal and Rumbi) (n = 20 each) reared in Algerian area steppe, were studied. The ewes were balanced for age and weight. All were in middle period of lactation. Individual milk samples were taken from each ewe third time from lactating period during spring season. Major elements of milk samples were slightly higher in milk from Rumbi than from Ouled-Djellal breeds. Results show that only Potassium, Sodium and Zinc were significantly influenced by breed type. Rumbi ewe’s milk gave the highest values (p ≤0.05) (1056±47.76, 667±79.75 and 7.7±0.99 ppm) than Ouled-Djellal ewes (974±18.83, 667±92.49 and 7.7±1.39 ppm, respectively). The average contents of trace elements in this study arranged according to the following order Zn